Rodyuk oleg. Features of tactics of interrogation in criminal proceedings - Rodyuk, Oleg (Archives of Criminology and Forensic Sciences, 2024)
The article examines the tactical aspects of conducting an interrogation as a key investigative action in criminal proceedings. The scientific problem of choosing methods and techniques to ensure the effective-ness of interrogation, taking into account the circumstances of the case and the individual characteristics of the interrogated person, is outlined. The aim of the study is to analyze the principles of preparation for interrogation, establishing psychological contact, adapting tactical techniques, and ensuring the legality and ethics of actions. An interdisciplinary approach was used, taking into account knowledge in the fields of psychology, criminology, sociology, and law. The main results confirm the importance of taking into account the psychological characteristics of individuals, the correct choice of communication methods and compliance with procedural norms. The conclusion is made about the need for a scientific approach to developing an effective interrogation strategy that contributes to obtaining high-quality information, respecting the rights of participants and avoiding manipulation.